Identification of the cassava NADP-ME gene family and its response and regulation in photosynthesis - Li, Haozheng; Xiao, Jin; Chen, Jiahui; Shen, Xu; Luo, Jia; Guo, Fengguang; Wang, Shangfei; Xu, Liangye; Guo, Xin; Wang, Shujuan; Wang, Haiyan; Wang, Wenquan (Frontiers in Plant Science, 2025)
NADP-malic enzyme (NADP-ME) is a crucial enzyme in C4 photosynthesis, responsible for the decarboxylation of malate in bundle sheath cells, enhancing the photosynthetic efficiency of C4 plants. Cultivated cassava exhibits high photosynthetic efficiency and biomass, and previous studies classify it as a C3–C4 intermediate type. The biomass of cassava correlates positively with photosynthetic rate, and the promoter region of MeNADP-ME3 contains insertion selected in cultivars different from wild ancestors. Four MeNADP-ME genes were identified in the cultivated cassava variety AM560, with promoter regions enriched in light-responsive elements. Phylogenetic and conserved domain analyses revealed that all subtypes are plastidic dicotyledonous types, closely related to AtNADP-ME4, with unique N-terminal domains in MeNADP-ME2 and MeNADP-ME3 specific to cassava, suggesting new functional roles. Subcellular localization showed predominant chloroplast localization, with greater involvement in leaf physiological processes in the cultivated variety SC205. These findings suggest that the NADP-ME family in cultivated cassava has been evolutionarily selected for photosynthesis. Further investigation revealed that MeNADP-ME3 is highly expressed in leaves and regulated by light intensity. Co-expression network analysis of shade-treated transcriptomes and transcription factor-promoter predictions showed that Indel sites in the MeNADP-ME3 promoter are bound by MeYABBY1, forming a regulatory network with other photosynthesis-related genes. This suggests that MeNADP-ME3 plays a role in C3–C4 intermediate photosynthesis during the evolution from wild to cultivated cassava, with other family genes also evolving towards photosynthetic functions. Our study lays the foundation for future functional research on the MeNADP-ME family and provides insights into the mechanisms underlying the high photosynthetic efficiency of cultivated cassava.